Advanced treatment of biologically pretreated coal gasification wastewater by a novel integration of heterogeneous Fenton oxidation and biological process. (April 2015) - Xu, Peng; Han, Hongjun; Zhuang, Haifeng; Hou, Baolin; Jia, Shengyong; Xu, Chunyan; Wang, Dexin
Highlights: FeO x were loaded on SBAC to serve as catalyst (FeO x /SBAC) in HFO. HFO eliminated COD and COLOR and improved biodegradability of wastewater. Surface reaction and hydroxyl radicals ( OH) oxidation were the mechanisms of HFO. The integration of HFO and BAF was more effective in abating pollutants. Abstract: Laboratorial scale experiments were conducted in order to investigate a novel system integrating heterogeneous Fenton oxidation (HFO) with anoxic moving bed biofilm reactor (ANMBBR) and biological aerated filter (BAF) process on advanced treatment of biologically pretreated coal gasification wastewater (CGW). The results indicated that HFO with the prepared catalyst (FeO x /SBAC, sewage sludge based activated carbon (SBAC) which loaded Fe oxides) played a key role in eliminating COD and COLOR as well as in improving the biodegradability of raw wastewater. The surface reaction and hydroxyl radicals ( OH) oxidation were the mechanisms for FeO x /SBAC catalytic reaction. Compared with ANMBBR–BAF process, the integrated system was more effective in abating COD, BOD5, total phenols (TPs), total nitrogen (TN) and COLOR and could shorten the retention time. Therefore, the integrated system was a promising technology for engineering applications.